A further contribution to the knowledge of Uroleucon species (Hemiptera, Aphididae) living on Adesmia (Fabaceae) in southern South America, with description of a new species from Chile - Durante, M. Pilar Mier; Ortego, Jaime; Von Dohlen, Carol D.; Nafría, Juan Manuel Nieto (Zootaxa, 2020)
Uroleucon (Hemiptera, Aphididae, Macrosiphini) is a highly diverse and widely distributed genus. Most of its species are hosted by plants of the Asteraceae or Campanulaceae, but three species from the southern end of South America have specialized to live on plants of the genus Adesmia (Fabaceae). New morphological and chorological data are provided for U. adesmiae Mier Durante and Ortego and U. naheulhuapense Nieto Nafría & von Dohlen, with a description of the alate viviparous female of the latter species. U. australe Nieto Nafría & Mier Durante, sp. n. is described from apterous viviparous females, oviparous females and males from four localities in the Chilean regions of Aysén and Magallanes; it is very close to U. nahuelhuapense, both morphologically and genetically. Contrary to what is typical for aphids, the males of U. australe have a greater number of distinguishing characters than are found in viviparous females. A modification of the identification key to the apterous viviparous females of the known Uroleucon species in South America by Nieto Nafría et al. (2019) is presented.